(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Around the world, online learning as well as classes are becoming a bigger part of the educational system. COVID-19 has caused a tremendous upheaval in the educational system, not only in India but globally. Virtual classes have replaced real classrooms at institutions all around the world, including in India. While technology makes things easier and more accessible, it may sometimes be restrictive, especially in India, where many students do not have access to the internet. As a result, there are issues with attendance and interest in online sessions, making online education channels difficult to adopt. Online learning satisfaction is an important factor in supporting effective educational processes. Despite the fact that online learning is the sole option during the COVID-19 epidemic, student and teacher satisfaction is critical to a successful and effective learning experience. This study focus on the Digital mode classes throughout COVID -19 and its level of satisfaction on online Education among school students in Delhi NCR region. The outcomes of the research show that online courses and e-learning apps have a significant impact on the everyday life of young people. Because online classes are so popular, they should be seen as a supplement and a great way to study throughout the outbreak. The future aspects are, you may learn in a relaxed setting with online education as well as online learning is not only one of the most effective solutions for students, but it is also more environmentally friendly.